HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN KEPERCAYAAN DIRI DALAM TUGAS PERKULIAHAN PADA MAHASISWA PENDIDIKAN IPS DI UNIVERSITAS TANJUNGPURA. - Herlin, Elvira Riasah; Aminuyati, Aminuyati; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the socio-economic status of parents, the level of confidence in lecture assignments and the relationship between parents' socio-economic status and confidence in lecture assignments for students of the Social Sciences Education study program at Tanjungpura University. The research approach used is quantitative in the form of correlation. The data collection tool used is a questionnaire or questionnaire. The number of respondents was 83 social studies education students. The data analysis technique used is descriptive statistics, correlation test and hypothesis testing. The results showed that the average socio-economic status of the parents of social studies education students was in the moderate category (69.90%), the level of confidence in lecture assignments for social studies education students was in the high category (81.36%) and there was no significant relationship between the socio-economic status of parents and confidence in lecture assignments for IPS Education students at Tanjungpura University, namely tcount ttable (1.097 1.989) which means H0 is accepted and Ha is rejected.